Consumption Patterns in the Digital Age: Changing Consumers Behavior Affects the Global Economy - Maleha, Nova Yanti; Umar, St Hafsah; Kotngoran, Wiljan Atfentia; Huda, Miftakhul (Nomico, 2025)
The development of digital technology has brought about significant changes in the consumption patterns of the global community. In the digital era, consumers increasingly rely on e-commerce platforms, social media and app-based services to fulfill their needs. This research aims to explore how changes in consumption patterns in the digital era affect consumer behavior and its impact on the global economy. This research uses a qualitative approach with a case study design and descriptive analysis to analyze the impact of economic digitalization on consumer consumption patterns, as well as the changes that occur in the business sector, especially in developing countries. The research found that digital consumers tend to be more informed, demand personalization, and care more about sustainability issues. E-commerce is a key element that is changing the way consumers interact with the market. In addition, digitalization is driving innovation in global business models, although it poses challenges such as digital inequality and data privacy. The results of this study provide important insights for governments and businesses to design strategies that are inclusive, sustainable and innovative. Policies and technological innovations need to be geared towards supporting changing consumption patterns, mitigating the challenges of digitalization, and capitalizing on global economic opportunities.